The Effect of Motivation on Employee Performance: A Case of Gambia Ports Authority in The Gambia - Ndow, Oulaye; Fanneh, Momodou Mustapha; Badjie, Gibriel (Proceeding Kilisuci International Conference on Economic & Business, 2024)
Research aim: This study aimed to assess the influence of motivation on employee performance within the Gambia Ports Authority (GPA). Design/Methode/Approach: A descriptive survey design was employed, utilizing structured questionnaires to gather primary data. The study employed simple random sampling to select participants. Statistical analysis was conducted using SPSS software, including reliability testing via Cronbach’s Alpha, Pearson’s correlation, and multiple regression analysis to test hypotheses. Research Finding: The research highlights the significant impact of various motivational factors on employee performance within GPA. Training, organizational prioritization, and investment in development programs were found to positively influence performance (89.10%). Additionally, positive working conditions (81.70%), employee recognition (79.90%), and delegation of responsibility (74.90%) were identified as crucial contributors to an optimal work environment. The study also underscores the motivating effects of salary, bonuses, and benefits, emphasizing the importance of compensation structures. Moreover, positive relationships with superiors, peer dynamics, and effective management styles were recognized as pivotal in driving employee performance and organizational success. Theoretical contribution/Originality: This study contributes to the understanding of the relationship between motivation and employee performance, specifically within the context of GPA. It emphasizes the importance of various motivational factors and their impact on organizational outcomes. Practitioner/Policy implication: The findings suggest the necessity for GPA to implement a comprehensive strategy addressing motivational factors to cultivate a highly productive workforce. Recommendations include conducting a thorough assessment of the current motivational landscape within the organization to identify challenges and barriers hindering high motivation levels. Research limitation: One limitation of this study is its focus on GPA, which may limit the generalizability of findings to other organizational contexts. Additionally, reliance on self-reported data through questionnaires may introduce response bias.